2019
DOI: 10.2147/cmar.s227961
|View full text |Cite
|
Sign up to set email alerts
|

<p>Image-Guided Percutaneous ‎Microwave Ablation Versus Cryoablation For Hepatocellular Carcinoma In High-Risk Locations: Intermediate-Term Results</p>

Abstract: ObjectiveThe aims of this study were to compare the clinical outcomes between image-guided percutaneous microwave ablation (MWA) and cryoablation (CRA) in patients with hepatocellular carcinoma (HCC) in high-risk locations and to identify the prognostic factors associated with the two treatment methods.MethodsThis retrospective study was institutional review board approved. A total of 120 patients (88 men and 32 women) with one hundred and thirty-four HCC lesions in high-risk locations from April 2014 to March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Major complications occurred in 5.4% of the 92 patients, with no procedure-related mortality. Our results are consistent with previous studies [ 9 , 26 ], and provide a further clinical reference for the application of percutaneous ablation in the treatment of HCC located adjacent to major organs or viscus.…”
Section: Discussionsupporting
confidence: 92%
“…Major complications occurred in 5.4% of the 92 patients, with no procedure-related mortality. Our results are consistent with previous studies [ 9 , 26 ], and provide a further clinical reference for the application of percutaneous ablation in the treatment of HCC located adjacent to major organs or viscus.…”
Section: Discussionsupporting
confidence: 92%
“…Full-texts for 259 articles were retrieved for detailed reviews and assessments. Notably, a total of 214 records were excluded, and 45 articles [ 20 , 43 85 ] involving 11,364 patients were included in the final analysis. All included studies reported on overall survival outcomes for patients.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding comparison of cryoablation to MWA, there is very little literature comparing these two modalities, and most noticeably cryoablation has not been compared with MWA in an RCT to the authors' knowledge. Hu et al 34 performed a retrospective comparison of outcomes of cryoablation (56 patients) to MWA (64 patients) for HCC and found that recurrence-free survival and OS were not significantly different between the two groups, but LTP and major complications were significantly lower in the cryoablation group ( p = 0.003 and p = 0.039, respectively). Finally, a recent meta-analysis by Gupta et al 8 compared outcomes of RFA, MWA, and cryoablation for HCC using comparative studies (randomized and non-randomized) with at least two arms comparing at least two of the three modalities.…”
Section: Comparison Of Cryoablation To Radiofrequency Ablation and Mi...mentioning
confidence: 99%